Breaking the rules : trading performance for intimacy with God - Anderson, Fil. (Downers Grove, Ill. : IVP Books, 2010)
In Breaking the rules, Fil invites us to explore what happens when good religion turns bad. At that time we are faced with expectations of what it takes to be "right with God"--whether it is the expectations of others, holding up under pressure, fixing what's wrong or accomplishing big things for God. When we set aside this false agenda, we find the courage to confess our fears and insecurities. We taste the depths of God's love for us. Here is an opportunity to quit trusting in our own ability to live for God, and simply trust in God instead.
Introduction: Breaking the rules -- Is your faith in God or religion? -- The myth that Jesus thinks like us -- Beauty in brokenness -- What's a picture worth? -- Right rules or right relationship? -- Worse than blindness -- Why this waste? -- Doing what we can -- The gift of memory -- Throwing in the towel on religion.
Includes bibliographical references (p. [235]-240).
Keywords: Spirituality